JAPANESE PUBLIC DIPLOMATION IN CHANGING NATION BRANDING THROUGH THE NIHONGO PARTNERS PROGRAM IN INDONESIA, 2014-2019: JAPANESE PUBLIC DIPLOMATION IN CHANGING NATION BRANDING THROUGH THE NIHONGO PARTNERS PROGRAM IN INDONESIA, 2014-2019 - Enggar Wiganti Laras; Laode Muhammad Fathun; Sindy Yulia Putri (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2020)
his research discusses how Japanese public diplomacy through the Nihongo Partners program to change nation branding in Indonesia in 2014-2019. The strategy undertaken by Japan with public diplomacy with Indonesia as a partner is due to the tenuous relations between Japan and countries in the Southeast Asia Region, one of which is Indonesia. On Post World War II, Japan tried to rise and finally succeeded to become developed country. However, the inherent bad history of colonizing countries in ASIA, the Malari Incident, and the dominance of Japan that unsettled the public, Japan has a desire to improve the image of Japan with soft power namely culture and education. Established the Japan Foundation as a government agency that aims to spread Japanese culture abroad through activities carried out by JF. In this program through the Japan Foundation in collaboration with the Government of Indonesia through the Ministry of Education and Culture of the Republic of Indonesia as a bridge between the two countries in carrying out this program. Through the Nihongo Partner program, Japan is trying to do public diplomacy to change the nation’s image of their country from a country that has a bad image into a peaceful and friendly country. This effort is Japan's way of realizing the nation's branding to emphasize that Japan has changed for the better and is given international trust in Japan with the aim of providing a good image, vision and mission, their way of life and Japanese cultural values. Keywords: Public Diplomacy, Cooperation, Nation Branding, Culture, Education.